Storage Stability Analysis on Microcapsules Pitaya Pigment Powders Under Different Condition - Ruri Aditya Sari (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Red Pitaya fruit (Hylocereus polyrhizus) known as an attractive source of natural red colourant for food application. The extraction of betacyanin pigment was extracted from the flesh of red pitaya fruits grown in Malaysia by using water as the extracting solvent and Rohapect 1BL was used to clarify the pigment extract. Microcapsules Pitaya Pigment Powders were prepared by using combination of Maltodextrin 10 DE and 25 DE with ratio (1:2). The objective of this study was to analyze the storage stability (color retention, pigment retention and kinetic degradation) on pitaya pigment powders on light and dark condition of storage for 24 weeks. The effect of Ascorbic acid at two concerntrations (0.1 % and 1.0%) were also investigated. The results showed that addition of different amount of ascorbic acid did not affect to L* values. The changes of L* values in sample with the addition ascorbic acid (0.1 % and 1.0 %) was ranged from 0.31 to 0.34. Samples with 1.0 % ascorbic acid at 0 % and 32 % RH, their half lives were both shorter (26.7 months and 20.0 months, respectively. Based on the results showed that red pitaya pigment powders were stable upon storage until 24 weeks and it could be as an alternative source of red colourant.